2023
DOI: 10.1186/s12967-023-04279-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of OPN contributes to idiopathic pulmonary fibrosis and indicates a poor prognosis

Jie Ji,
Shudan Zheng,
Yuxin Liu
et al.

Abstract: Background Idiopathic pulmonary fibrosis (IPF) is fibrotic lung disease with no effective treatment. It is characterized by destruction of alveolar structure and pulmonary interstitial fibrosis, leading to dyspnea and even asphyxia death of patients. Epithelial-mesenchymal transition (EMT) is considered to be a driving factor in the pathogenesis of IPF. Osteopontin (OPN) is a secreted protein widely present in the extracellular matrix and involved in the occurrence and development of a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Survival analysis also demonstrated that patients with OPN ≥ 25ng/ml had a higher incidence of organ damage. In idiopathic pulmonary brosis, OPN is involved in in ammatory response, ECM deposition and epithelial-mesenchymal transition [19].OPN is associated with poor prognosis of pulmonary brosis [20].OPN is produced by a variety of cell types, including B cells, T cells, natural killer cells, macrophages, neutrophils, dendritic cells(DCs), bone cells, epithelial cells, and neuronal cells. Binding of OPN to integrin or CD44 is involved in immune response and brosis [21].In terms of immune response, the interaction between OPN and CD44 in Th cells enhances the differentiation of Th1 and Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Survival analysis also demonstrated that patients with OPN ≥ 25ng/ml had a higher incidence of organ damage. In idiopathic pulmonary brosis, OPN is involved in in ammatory response, ECM deposition and epithelial-mesenchymal transition [19].OPN is associated with poor prognosis of pulmonary brosis [20].OPN is produced by a variety of cell types, including B cells, T cells, natural killer cells, macrophages, neutrophils, dendritic cells(DCs), bone cells, epithelial cells, and neuronal cells. Binding of OPN to integrin or CD44 is involved in immune response and brosis [21].In terms of immune response, the interaction between OPN and CD44 in Th cells enhances the differentiation of Th1 and Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…OPN, a phosphorylated glycoprotein, which expressed in the mineralized extracellular matrix (ECM) of bone in normal tissues cells such as fibroblasts, osteoblasts, and osteocytes. 150 , 151 As one of the classical and important ligands of CD44, OPN affects the proliferation and invasion of tumor cells as well as inflammation in normal cells, by regulating related signaling pathways. 150 , 152 Activation of the JUN N‐terminal kinase pathway has been shown to contribute to the promotion of clonogenicity and tumor growth in a xenograft model via OPN secreted by tumor‐associated macrophages.…”
Section: Cd44 In Neoplastic Diseasesmentioning
confidence: 99%
“…Studies in PCLS have supported a number of different molecules in the pathogenesis of IPF including: a transmembrane protein that can interact with growth factor receptors or extracellular ligands to modulate receptor activation [104]; activation of histone deacetylases [105]; activation of integrins [106]; ion channel activation [107]; a kinase and a signaling microdomain protein [108]; a protein involved in cell fate determination, motility, and organogenesis [109]; and even an miRNA mimic as a potential therapy [110]. Additionally, other pathways have been postulated to be part of specific aspects of the biology of both epithelial cells and fibroblasts that may play a role in the pathology of IPF [111][112][113][114][115][116][117][118][119][120][121]. Studies have utilized PCLS to identify the cell types that drive fibrosis signals and showed the ways in which PCLS can model IPF [122][123][124][125].…”
Section: Studies In Fibrotic Lung Diseasesmentioning
confidence: 99%